Technical Analysis of the Geedge Networks Firewall Source Code Leak - Ablove, Anna; Walker, Johnnie; Wolin, Ben; Niere, Niklas; Graf Lange, Felix; Ortwein, Aaron; Huremagic, Armin; Priyanka, Richa; Zohaib, Ali; Sheffey, Jade; Heitmann, Nico; Halderman, J. Alex; et al.
In September 2025, over 100K internal documents (including code, communications, etc.) from Geedge Networks, a Chinese DPI company with ties to the Great Firewall of China, were leaked to the public. In this paper, we analyze the source code from this leak, focusing on Geedge Networks’ flagship product, the Tiangou Secure Gateway (TSG) firewall. Working across multiple repositories, we successfully build and run a local copy of TSG—revealing key aspects of its architecture, including the protocols it is capable of parsing and the format of blocking rules used to censor sites, proxies, and other resources. Finally, we extract several fingerprints from TSG, including custom random number generators and parsing idiosyncrasies that allow us to identify its use and similar deployments in the Great Firewall of China. This is the first time that the source code of a commercial DPI has been leaked, and our work is the first code analysis of a core firewall component used in national censorship infrastructure. This unprecedented investigation offers insights that can assist circumvention developers and Internet security researchers in further understanding the capabilities and limitations of modern censorship technology.

On Russia’s Early Introduction of QUIC SNI Censorship - Heitmann, Nico; Niere, Niklas; Graf Lange, Felix; Somorovsky, Juraj
Governments around the world limit free access to information through Internet censorship. With the rising adoption of the QUIC protocol, these censors have been forced to evolve their systems. Russia introduced sweeping changes to its censorship after its full-scale invasion of Ukraine, including completely blocking international QUIC connections. However, after this broad filter was identified in 2022, Russian QUIC censorship received little attention: The current state of QUIC censorship by TSPU devices is largely unknown. In this paper, we provide a timeline of Russian QUIC censorship and detail its current state. We identify that Russian TSPU devices switched to SNI-dependent QUIC censorship on a large scale between May 2022 and July 2023, a fact that went largely unnoticed for three years. While the GFW was previously thought to be the first censor with broad SNI-dependent QUIC censorship, we highlight that Russian TSPU devices broadly adopted SNI-dependent QUIC censorship at least nine months before the GFW. We consider this an indicator of the TSPU devices’ flexibility and of Russia’s willingness to invest in strict and up-to-date censorship.

When Trying Harder Helps: Effort Instructions Affect Performance in Complex Motor Tasks - Böer, Nils Tobias; Steinborn, Michael B.; Weigelt, Matthias; Güldenpenning, Iris (Abstracts of the 68th Conference of Experimental Psychologists)
Keywords: effort; try-harder instruction; deception; sport psychology; action and perception

From interference to priming? Reinterpreting the head-fake effect in basketball through continuous measurements - Güldenpenning, Iris; Schulze Frielinghaus, Lars; Böer, Nils Tobias; Weigelt, Matthias (Abstracts of the 68th Conference of Experimental Psychologists)

Strategic adaptations to deceptive actions in sports: The anticipation-response-inhibition-accuracy trade-off - Wickemeyer, Carolin; Weigelt, Matthias; Güldenpenning, Iris (Journal of Sport and Exercise Psychology)

The role of domain-specific expertise on response inhibition in the basketball-specific ARI-task - Wickemeyer, Carolin; Güldenpenning, Iris; Meyer, Johannes; Klatt, Stefanie; Weigelt, Matthias (Abstracts of the 68th Conference of Experimental Psychologists)

Rapid chase or continuous flow of information? Visual-motor processing of head fakes in basketball - Güldenpenning, Iris; Schulze Frielinghaus, Lars; Böer, Nils Tobias; Weigelt, Matthias (Abstracts of the 58th Annual Conference of the German Association of Sport Psychology)

The role of domain-specific expertise on response inhibition in the basketball-specific ARI-task - Wickemeyer, Carolin; Güldenpenning, Iris; Meyer, Johannes; Klatt, Stefanie; Weigelt, Matthias (Abstracts of the 58th Annual Conference of the German Association of Sport Psychology)

Efficient Silicon Nitride Quantum Interconnect for Intrinsic Silicon Nitride Single-Photon Emitters - Farheen, Henna; Chen, Yuheng; Chen, Peigang; Maan, Pranshu; Peana, Samuel; Senichev, Alexander; Shalaev, Vladimir M.; Boltasseva, Alexandra; Förstner, Jens; Kildishev, Alexander V. (IEEE Journal of Selected Topics in Quantum Electronics)
Keywords: tet_topic_opticalantenna

Predictors of primary school students’ prosocial behaviour toward peers with social-emotional difficulties in inclusive education: Insights from the Theory of Planned Behaviour. Individual Paper Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. - Löper, Marwin Felix; Knickenberg, Margarita; Hellmich, Frank

Teachers’ conceptualizations of social-emotional competencies in cooperative learning: Insights from inclusive primary school classrooms. Individual Paper Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. - Knickenberg, Margarita; Funk, Michael; Casamassima, Gianna; Löper, Marwin Felix; Hellmich, Frank

Social and emotional competencies for cooperative learning in inclusive primary education: A project overview. Poster Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. - Casamassima, Gianna; Funk, Michael; Knickenberg, Margarita; Löper, Marwin Felix; Grosche, M.; Zimmer, L.; Grüßing, M.; Wess, N.; Hellmich, Frank

Prokrastination: Erkennen, Verstehen, Reduzieren

Photovoltaik Alles-in-einem-Band für Dummies - Krauter, Stefan; Froitzheim, Armin

Variationen eines Systemalptraums: Postmigrantische Befindlichkeiten in Burhan Qurbanis "Berlin Alexanderplatz" und Visar Morinas "Exil" - Morrien, Rita (Grenz(über)fälle und Grenzgänge: Literatur, Kunst und gesellschaftliche Dynamiken ab 2000)
Sowohl in Burhan Qurbanis "Berlin Alexanderplatz" als auch in Visar Morinas "Exil" werden Paradoxien der postmigrantischen Gesellschaft mittels einer filmischen Ästhetik des Traums reflektiert. In Qurbanis radikaler Aktualisierung von Döblins Berlin "Alexanderplatz" ist die Hauptfigur ein Schwarzer Geflüchteter, der in Deutschland auf einen Neuanfang als ‚anständiger Mensch‘ hofft. Morinas Exil erzählt die Geschichte eines scheinbar vorbildlich integrierten Migranten, der sich plötzlich als Opfer von Rassismus erlebt. Die Filme werden hier als Variationen eines Systemalbtraums gelesen, weil in beiden Fällen die kollektiven Ängste der Dominanzgesellschaft vor dem ‚parasitären Anderen‘ und die Idee der pluralen Demokratie zur Kollision gebracht werden.
Keywords: Postmigrantischer Film; Traumästhetik; Burhan Qurbani; Berlin Alexanderplatz; filmische Adaption; Visar Morina

Impulse zur Stochastik in der Oberstufe - Biehler, Rolf; Binder, Karin; Haverkamp, Michael; Kempen, Leander (Mathematikabitur „Status Quo–Quo Vadis “: Tagungsband zur Fachtagung zum Mathematikabitur am 11./12. Februar 2025 in Dresden)

Organisationen, Konventionen und Kritik. Der französische Neopragmatismus in der Organisationsforschung - Knoll, Lisa (Handbuch Organisationssoziologie)

"Future Fresko" - Charlotte Kraffts Münsterland-Blog MOMUMENT als dystopische Heimatliteratur - Morrien, Rita (Literatur in Westfalen. Beiträge zur Forschung 22)

‘School is no longer a lone wolf effort’: leadership strategies for inclusive, community-based school cultures - Woodcock, Stuart; Avramidis, Elias; Sharma, Umesh; Subban, Pearl; Sahli Lozano, Caroline; Kullmann, Harry; Loreman, Tim; Wüthrich, Sergej; Knickenberg, Margarita (School Leadership & Management)
Based on the premise that the successful implementation of inclusion is largely dependent on the educators’ commitment to inclusive ideals, this study sought to examine the ways principals promote an inclusive vision and foster the development of associated practices in their school community. The study employed an exploratory qualitative research design, collecting data through semi-structured interviews and focus groups with 12 principals of highly-ranked inclusive schools from four countries: Australia, Italy, Switzerland, and Spain. In so doing, the emphasis was placed on the principals’ perspectives and practices that contribute to the development of an inclusive school culture. The iterative process of thematic analysis revealed five broad key factors that affect and impact school inclusivity, namely: institutional commitment to a collective inclusive culture; family partnership and co-responsibility; collaboration among key stakeholders (e.g. students, teachers, other staff); students’ voice and agency; and building and sustaining inter-institutional partnerships. This paper concludes by advocating a community-based approach model to school inclusion by identifying key factors on which principals can rely to navigate material, social, and political challenges.
Keywords: Inklusive Bildung; Schulentwicklung; Schulleitung; Gemeinschaftlichkeit; Haltung

Interkulturelle Pädagogik: Fallstricke, Potenziale und Forschungsgegenstände - Pöllmann, Andreas
Das Fachbuch ermutigt dazu, eingefahrene Denkweisen zu hinterfragen und neue pädagogische Handlungsspielräume zu erschließen. Es verbindet theoretische Kontroversen mit praxisnahen Fragestellungen und eröffnet so einen Zugang zu aktuellen Debatten in Bildung und Gesellschaft. Die innovativen Konzepte der kulturellen Pluriformität und der intersektionalen Interkulturalität ermöglichen differenzierte Denk- und Handlungsperspektiven jenseits vereinfachender Kulturbegriffe. Weitere Alleinstellungsmerkmale des Buches sind die reflektierte Auseinandersetzung mit einschlägigen Fallstricken, Potenzialen und Forschungsgegenständen sowie die konsequente Einbeziehung englischsprachiger und spanischsprachiger Fachliteratur. Das komplexe Feld wird nicht vereinfacht, sondern in seiner Widersprüchlichkeit und Vielschichtigkeit ernst genommen. Dabei lädt das Buch dazu ein, pädagogische Routinen kritisch zu reflektieren, vermeintliche Selbstverständlichkeiten zu irritieren und solidarisches Handeln zu fördern. Es bietet Impulse für eine emanzipatorische interkulturelle Pädagogik, die zu Multiperspektivität, Gerechtigkeit und solidarischem Zusammenleben beiträgt.